STRATEGI PEMASARAN JASA PENDIDIKAN PADA PONDOK PESANTREN - Mohamad Mustafid Hamdi (Asosiasi Dosen Tarbiyah STAI Darussalam Nganjuk, 2021)
Marketing is one of the main activities that need to be done by the company, be it a company of goods or services in an effort to maintain the survival of its business. Marketing comes from the basic word market, the term market is composed of all potential customers who have certain needs or wants and are willing and able to participate in the exchange to meet those needs or wants. The size of the market depends on the number of people who have needs, have resources that others are interested in, and are willing to offer those resources to be exchanged in order to meet their needs. Pondok Pesantren in its journey until now, as a social foundation, pesantren has organized formal education in the form of both public schools and religious schools. In addition, pesantren also organizes non-formal education in the form of madrasah diniyah which teaches the fields of religious science only. Pesantren has also developed its function as a foundation of social solidarity by accommodating children from all walks of life and providing equal services to them, regardless of their socioeconomic level.